External Shariah auditing in Islamic banks: what do internal auditors think? - Mohd Haridan, Nurfarahin; Sheikh Hassan, Ahmad Fahmi; Mohammed Shah, Sabarina (Emerald Publishing, 2024)
Purpose: This study aims to investigate the pragmatic issues on the radical call for the establishment of an external Shariah auditor (ESA) in the governance framework of Islamic banks (IBs). Design/methodology/approach: From 11 well-established Malaysian IBs, 16 internal auditors were interviewed to provide an in-depth understanding on how ESA can provide greater assurance to stakeholders in Malaysian IBs. Findings: This study reported mixed acceptance from internal auditors on the proposed additional governance layer to be undertaken by the ESA. Generally, internal auditors reluctantly agreed that Shariah auditing by the ESA would enhance the quality of Shariah assurance but maintain several practical concerns regarding lack of guidelines on Shariah auditing, the additional cost to be borne by IBs and the possible tensions between the ESA and Shariah board (SB) amid the diverse Shariah interpretations available for experts in the field. Practical implications: The critical point on the manifestation of an ESA in the contemporary IB practice brought by this study highlights the need for regulation and policy promulgation that embrace a comprehensive approach to Shariah audit process within the religio-ethical dogma of Islamic banking and the pragmatic approach to banking. Originality/value: This study provides evidence on the expected role and competency of an ESA and explores the implications produced by its implementation in Malaysian IBs. This study also clarifies how IBs should delineate the role of Shariah assurance from SB to ESA.